2011
DOI: 10.1176/appi.ajp.2011.10071062
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in the Balance Between Goal-Directed Behavior and Habit Learning in Obsessive-Compulsive Disorder

Abstract: Objective:Obsessive-compulsive disorder (OCD) is characterized by repetitive, ritualistic behaviors and thought patterns. Although patients with OCD report that these compulsive behaviors are unproductive and often senseless, they are unable to desist. This study investigated whether the urge to perform compulsive acts is mediated by a disruption in the balance between flexible, goal-directed action control and habitual behavior.Method:A total of 21 patients with OCD and 30 healthy comparison subjects particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
479
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 524 publications
(554 citation statements)
references
References 44 publications
41
479
5
1
Order By: Relevance
“…These findings extend previous research documenting a bias toward habits among OCD patients (Gillan et al, 2011). However, these correlational data cannot determine the causal role of bias toward habits in OC symptoms, and longitudinal research examining aberrant habit learning as a risk factor for OCD are warranted.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…These findings extend previous research documenting a bias toward habits among OCD patients (Gillan et al, 2011). However, these correlational data cannot determine the causal role of bias toward habits in OC symptoms, and longitudinal research examining aberrant habit learning as a risk factor for OCD are warranted.…”
Section: Discussionsupporting
confidence: 61%
“…According to the habit hypothesis of OCD (Graybiel and Rauch, 2000;McDonald et al, 2004;Robbins et al, 2012), compulsive symptoms are caused by deficits in goal-directed learning, which lead to excessive reliance on stimulus-response habits. In support of this hypothesis, Gillan et al (2011) found that OCD patients, compared to healthy volunteers, underutilized goal-directed action control and relied excessively on habits during instrumental responding.…”
Section: Introductionmentioning
confidence: 87%
“…In other words, the paradigm is effective regardless of the direction of change in motivational or affective valence. Maladaptive associative memories are involved in the pathology of several psychiatric disorders besides addiction, such as phobias (Mineka and Ohman, 2002), post-traumatic stress disorder (Desmedt et al, 2015), and obsessive-compulsive disorder (Gillan et al, 2011). Therefore, utilizing the retrieval-counterconditioning procedure to replace these unwanted memories with adaptive memories is a potentially novel behavioral therapeutic approach for these neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Along the same lines, amphetamine pre-treatment speeds up the rate at which the outcome insensitivity develops (Nelson and Killcross, 2006), and this depends particularly on D 1 rather than D 2 receptors (Nelson and Killcross, 2013). In humans, there is evidence for enhanced habitization in obsessive-compulsive disorder (Everitt and Robbins, 2005;Robbins et al, 2012;Gillan et al, 2011Gillan et al, , 2013 and forthcoming evidence in cocaine addiction (N. Daw and V. Voon, personal communication), but not yet in alcohol addiction (Sebold et al, subm).…”
Section: Individual Variability In Addiction Vulnerabilitymentioning
confidence: 96%
“…It is important, though, to bear in mind that although habits share features with compulsions (Gillan et al, 2011(Gillan et al, , 2013, they are not one and the same (Dayan 2009;Robbins et al 2012 and many others). It has been suggested that after extended training, habits become deeply engrained by shifting further dorsally in the corticostriatal loops (Belin and Everitt, 2008;Willuhn et al, 2012).…”
Section: Shifts Towards Model-free Learning In Addictionmentioning
confidence: 99%